2012
DOI: 10.1016/j.diagmicrobio.2012.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Can mailed swab samples be dry-shipped for the detection of Chlamydia trachomatis, Neisseria gonorrhoeae, and Trichomonas vaginalis by nucleic acid amplification tests?

Abstract: Background Dry-shipped and mailed vaginal swabs collected at home have been used in research studies for the detection of C. trachomatis (CT), N. gonorrhoeae (GC), and Trichomonas vaginalis (TV) by nucleic acid amplification tests (NAATs) in screening programs. A verification study was performed to compare the limit of detection of CT, GC, and TV on swabs that were dry-shipped to paired swabs that were wet-shipped in transport media through the U.S. mail. Methods The Centers for Disease Control and Preventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 27 publications
1
19
0
Order By: Relevance
“…Our results show that the RNA target detected using the ACT is very stable on dry swabs under relatively high temperatures for an extended period of time, as previous studies had demonstrated (10,11,15). These findings suggest that the combination of the dry swab and the Aptima test may be suitable for use when specimens are collected in unfavorable settings, where ambient temperatures may be high and transport difficult.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Our results show that the RNA target detected using the ACT is very stable on dry swabs under relatively high temperatures for an extended period of time, as previous studies had demonstrated (10,11,15). These findings suggest that the combination of the dry swab and the Aptima test may be suitable for use when specimens are collected in unfavorable settings, where ambient temperatures may be high and transport difficult.…”
Section: Discussionsupporting
confidence: 66%
“…However, SOVS specimens are FDA cleared for use only when collected in a clinic setting. The ability to self-collect at home and mail in specimens could have a significant impact on sexually transmitted disease (STD) control efforts (13)(14)(15). To assess such use in screening programs, we initially performed a pilot study to determine specimen stability and monitor the shipping temperatures during transit.…”
mentioning
confidence: 99%
“…It has been shown that self-collected samples are able to provide the same sensitivity as those samples collected in clinics. 4 In urine, the average CT load was 770 EBs per 100 μl samples for women and 1200 EBs per 100 μl for men. 5 …”
Section: Introductionmentioning
confidence: 98%
“…Upon arrival, dry-shipped vaginal swabs were expressed into 800 μL of 1X TE buffer pH 7.4 and split into 2 aliquots, 1 containing 200 μL and 1 containing 400 μL, then 200 μL was transferred into a vaginal APTIMA collection tube for testing (Gaydos et al, 2012; Masek et al, 2009). Vaginal swabs were tested individually by AC2 and later pooled for analysis by GeneXpert.…”
mentioning
confidence: 99%